Actions of Retinoic Acid in the Pathophysiology of HIV Infection - Sidell, Neil; Kane, Maureen A. (Nutrients, 2022)
The vitamin A metabolite all-trans retinoic acid (RA) plays a key role in tissue homeostasis and mucosal immunity. RA is produced by gut-associated dendritic cells, which are among the first cells encountered by HIV. Acute HIV infection results in rapid reduction of RA levels and dysregulation of immune cell populations whose identities and function are largely controlled by RA. Here, we discuss the potential link between the roles played by RA in shaping intestinal immune responses and the manifestations and pathogenesis of HIV-associated enteropathy and similar conditions observed in SIV-infected non-human primate models. We also present data demonstrating the ability of RA to enhance the activation of replication-competent viral reservoirs from subjects on suppressive anti-retroviral therapy. The data suggest that retinoid supplementation may be a useful adjuvant for countering the pathologic condition of the gastro-intestinal tract associated with HIV infection and as part of a strategy for reactivating viral reservoirs as a means of depleting latent viral infection.